The Application of the Demonstration Model in Social Studies Learning to Improve Learning Outcomes in Grade IV of Public Elementary School 15 in Serang - Junaesih, Junaesih; Kurniawati, Ajeng; Humairoh, Humairoh (Jurnal Primagraha, 2023)
This study aims to improve learning outcomes in grade IV SD Negeri 15 Serang by applying demonstration methods in social studies learning.  This study discusses the implementation of demonstration methods to improve student learning outcomes. The library research method used a qualitative descriptive approach. The results of this study from several theses and journals show that demonstration methods can improve student learning outcomes. As for the obstacles faced by several writers Humairoh,Junaesih, Ajeng kurniawati.. namely the delivery of teacher material that is still lacking, and the lack of teaching aids available in the madrasah, and limited time is limited.